2015
DOI: 10.1186/s40824-014-0026-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of biphasic calcium phosphate and biphasic calcium phosphate collagen composite on osteoconductive potency in rabbit calvarial defect

Abstract: BackgroundThe aim of this study was to determine the osteoconductivity of biphasic calcium phosphate collagen composite (BCPC) in rabbit calvarial defect model by comparing with biphasic calcium phosphate (BCP). Four 8 mm diameter bicortical calvarial defects were made in ten rabbits. Each of the defects was randomly assigned and filled with 1) collagen sponge, 2) BCP, 3) BCPC, and 4) nothing as control. The animals were sacrificed at either 2 weeks (n = 5) or 8 weeks (n = 5) healing period.ResultsAll groups s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…It allows the progressive releasing of these factors, able to induce migration, adhesion and proliferation of cells inside the pore network and to promote a faster angiogenesis and a more effective osteo-genesis inside these pores (19)(20)(21). Theoretical data was confirmed by clinical outcome (22). In fact, according to several studies (23)(24)(25)(26), new generation hydroxya- (27).…”
Section: Discussionsupporting
confidence: 56%
“…It allows the progressive releasing of these factors, able to induce migration, adhesion and proliferation of cells inside the pore network and to promote a faster angiogenesis and a more effective osteo-genesis inside these pores (19)(20)(21). Theoretical data was confirmed by clinical outcome (22). In fact, according to several studies (23)(24)(25)(26), new generation hydroxya- (27).…”
Section: Discussionsupporting
confidence: 56%
“…37 The most commonly used calcium phosphate ceramics are HA and -TCP at various weight ratios. 41,42 The high biocompatibility, increase safety, high predictability, unlimited availability, low morbidity for patients, and cost-effectiveness of calcium phosphate ceramics all represent important advantages over autografts and allografts. 41,42 The high biocompatibility, increase safety, high predictability, unlimited availability, low morbidity for patients, and cost-effectiveness of calcium phosphate ceramics all represent important advantages over autografts and allografts.…”
Section: Discussionmentioning
confidence: 99%
“…[38][39][40] Calcium phosphate ceramics have shown bioactivity and osteoconductivity in previous papers. 41,42 The high biocompatibility, increase safety, high predictability, unlimited availability, low morbidity for patients, and cost-effectiveness of calcium phosphate ceramics all represent important advantages over autografts and allografts. 43 Although the ideal ratio of HA to -TCP is still under investigation, [44][45][46] variant ratios of BCPs have been widely used for bone graft substitutes, with favorable results A review of the commercially available BCP indicated that the most common ratio is 60% HA and 40% -TCP.…”
Section: Discussionmentioning
confidence: 99%
“…Bone graft materials are used as scaffold or filler to promote bone formation and wound healing. These materials are broadly divided into autograft, allograft, xenograft, and alloplast (Table 2), which act as a mineral reservoir to assist new bone formation [23,24]. [50].…”
Section: Oral Soft Tissue Wound Healingmentioning
confidence: 99%